Pola Strategi Investasi Investor Individu Saham Menurut Generasi X, Y, Dan Z - Elizabeth Lucky Maretha Sitinjak (The Indonesia Capital Market Institute, 2019)
Purpose- The purpose of this study, showing the pattern of stock investment strategy in accordance with the type of generation in order to manage the portfolio optimally. Methods- This research method using Anova with data obtained from Meta Data Analysis subjects of previous research experiments. Finding- The results show, each generation has a pattern of different stock investment strategies. This can be seen from the level of investor risk, and stock portfolio. The combination of stock portfolios tends to consist of private companies located in 10 sectors, private companies-BUMN, or private companies-BUMD. Generation X's investment strategy pattern tends to use the Momentum Strategy, Generation Y tends to use Top-Down Strategy, while Generation Z tends to use Buy-Hold and Momentum Strategies.